(untitled) (Nóema, 2025)
Artificial Intelligence in Jean Baudrillard’s The Intelligence of Evil or the Lucidity Pact Artificial intelligence works by transcribing the world mathematically. In this article, we want to analyze the issues raised by this modus operandi using the philosophy of the French philosopher Jean Baudrillard. What he’s most interested in, is that this mathematical transcription will lead to the loss of what makes the world a living organism, namely uncertainty, finitude, chaos. AIs are used to get ahead with this project to realized what Baudrillard defines «integral reality», a reality made transparent to eliminate any opacity that cannot be controlled. This crime against reality, committed by those who are afraid of the “shadows” that reality can have, is not perfect, because inside us we want to withstand this mathematical transcription of the world. This is the “lucidity” that a person, who witnesses the defeat of that dream of integrality, has: this mathematical transcription is destroyed by its own working.